Conjugal trajectories : relationship beginnings, change, and dissolutions - Cuevas Hernández, Ana Josefina; Blair, Sampson Lee (Contemporary perspectives on family research ;, 2023)
Many societies are experiencing substantial change in family forms and structures. For both families and individuals, conjugal trajectories continue to be a core element of life under the pressures of societal conventions, prompting many toward some variety of conjugal relationship. However, a combination of factors, including decreasing marriage and fertility rates and an increase in cohabitation and singlehood, have brought about more variety in conjugal relationships than ever before. Conjugal Trajectories: Relationship Beginnings, Change, and Dissolutions covers a wide range of topics related to conjugality including the growing rejection of marriage, the impact of education and employment, cultural perceptions of couple-hood, dating and relationship formation, migration and transnational conjugality, peer versus familial pressures, marriage-divorce-marriage trajectories, tradition versus modernity, generational differences, gender identities, divorce status, conjugal violence, aging, and parenthood. Multidisciplinary in scope and using predominantly qualitative approaches, Conjugal Trajectories: Relationship Beginnings, Change, and Dissolutions focuses upon relevant trajectories to better comprehend the evolving nature of conjugal relationships and its implications for family life moving forward.